2021
DOI: 10.1055/s-0041-1735583
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiological Study of Acinetobacter calcoaceticus baumannii with Special Reference to Multidrug Resistance

Abstract: Introduction The outbreak of Acinetobacter calcoaceticus baumannii (ACB) is mainly reported to be a notorious pathogens at health-care settings. It is the major problem on the health-care system with high morbidity and mortality rates because of the broad range of antibiotic resistance and lack of understanding the mechanism of developing new antibiotic resistance rapidly. It emphasizes the importance of local surveillance in describing or understanding and predicting microbial resistance patterns so that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The study for species-level identification of A. baumannii from previously phenotypically identified non-repetitive clinical isolates of 289 ACB complex [ 4 ] was conducted at the Department of Microbiology, IQ City Medical College Hospital, Durgapur, West Bengal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study for species-level identification of A. baumannii from previously phenotypically identified non-repetitive clinical isolates of 289 ACB complex [ 4 ] was conducted at the Department of Microbiology, IQ City Medical College Hospital, Durgapur, West Bengal.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous phenotypic study [ 4 ] clearly demonstrated that the ACB complex clinical isolates were resistant to the most potent drugs and further suggested its identification at the species level and association with resistance determinants at the genetic level. Therefore, this study was conducted to determine the incidence rate of A. baumannii from ACB complex clinical isolates and their resistance determinants responsible for β-lactamase in association with MDR A. baumannii as genotype analysis is reliable and valid.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation